Risk Management Practice Adopted in Road Construction Project - Hemant Gain; A. K. Mishra; P. S. Aithal (International Journal of Management, Technology and Social Sciences (IJMTS), 2022)
Purpose: Zero risk construction is only a dream not reality as there is nothing certainity in the real world and scientists are only capable of coverting the same into risk with high level data science. The practice of risk management is an attempt to highlight risk elements with a case of urban road construction in Sindhupalchowk district, Province 3, Nepal. Design/Methodology/Approach: The 5-point Likert scale questionnaire survey was done to collect the primary data. Risk Management Practice is documented based on survey response in percentage through charts and graphs. Field visit were done for visual assessment of the construction procedure along with key informant interview and Secondary data of Detail Project Reports, Design and Drawings were effectively analyzed. Cronbach’s alpha was used to measure the reliability and triangulations were done for validity. Findings/Result: The results from this research indicates that contractor’s organization are averagely aware with a mean score of 3.30 about Risk Management Practice and averagely practicing risk management formally with mean score of 2.83. They are averagely analyzing risk management techniques with mean score of 3.07. Mean score is slightly higher based on client’s perspective with score for awareness being 3.93 and score for risk management being practiced formally is 3.13. Risk analysis score based on client’s management is 3.40. Mostly adopted technique of risk identification is monitoring and evaluation report of similar past projects and direct judgment is widely used technique for risk assessment of road construction projects at Sindhupalchowk district based on both client’s and contractor’s perspective. Risk response strategy based on contractor’s perspective is monitoring the risk and preparing contingency plan whereas that for client is transfer of risk. Originality/Value: It is action research which is significant for professional to understand the practices of risk management being adopted by Nepalese Contractors in hilly region of Nepal. Paper Type: Ex-Post Facto Research